Affecting of Glyphosate Tolerance and Metabolite Content in Transgenic Arabidopsis thaliana Overexpressing EPSPS Gene from Eleusine indica - Jingchao Chen; Zhiling Li; Haiyan Yu; Hailan Cui; Xiangju Li (Plants)
Long-term use of the global non-selective herbicide glyphosate for weed control has caused resistance in weeds. Overproducing of the target of glyphosate 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) is one of the resistance mechanisms in weeds. However, few studies have measured the effects on tolerance levels and metabolite content in model plant species overexpressing EPSPS from weeds. We assessed the resistance levels of transgenic Arabidopsis thaliana overexpressing EPSPS from Eleusine indica, and its effects on metabolite content using the method of both quasi-targeted and targeted metabolomics. The results showed that the average resistance index of the transgenic lines was 4.7 and the exogenous E. indica EPSPS expression levels were 265.3- to 532.0-fold higher than those in the wild-type (WT) line. The EPSPS protein ranged from 148.5 to 286.2 μg g−1, which was substantially higher than that in the WT line (9.1 μg g−1). 103 metabolites associated with flavone and flavonol biosynthesis, the metabolism of aromatic amino acids, energy metabolism, and auxin synthesis were significantly higher in the transgenic glyphosate-resistant individuals (R) than in the WT individuals. The results of quantitative analysis show that pyruvate, sedoheptulose 7-phosphate, and gluconic acid amounts in R plants were 1.1-, 1.6- and 1.3-fold higher than those in WT plants, respectively. However, both citric and glyceric acid levels were 0.9-fold lower than those in WT plants. The abundance of other metabolites in the glycolytic and pentose phosphate pathways of central carbon metabolism was similar in the WT and transgenic plants. Glutamic acid was significantly more abundant in the transgenic line than in the WT plants. In contrast, asparagine, glutamine, and lysine were less abundant. However, the concentration of other amino acids did not change significantly. Overexpression of E. indica EPSPS in A. thaliana conferred a moderate level of tolerance to glyphosate. Metabolites associated with flavone and flavonol biosynthesis, the metabolism of aromatic amino acids, and energy metabolism were significantly increased. The results of this study will be useful for evaluating the characterisation and risk assessment of transgenic plants, including identification of unintended effects of the respective transgenic modifications.